2017
DOI: 10.1038/ncomms15277
|View full text |Cite
|
Sign up to set email alerts
|

Impaired prosaposin lysosomal trafficking in frontotemporal lobar degeneration due to progranulin mutations

Abstract: Haploinsufficiency of progranulin (PGRN) due to mutations in the granulin (GRN) gene causes frontotemporal lobar degeneration (FTLD), and complete loss of PGRN leads to a lysosomal storage disorder, neuronal ceroid lipofuscinosis (NCL). Accumulating evidence suggests that PGRN is essential for proper lysosomal function, but the precise mechanisms involved are not known. Here, we show that PGRN facilitates neuronal uptake and lysosomal delivery of prosaposin (PSAP), the precursor of saposin peptides that are es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 56 publications
8
106
0
Order By: Relevance
“…This will be of therapeutic interest for FTLD, since haploinsufficiency of PGRN is a leading cause of FTLD and impaired PSAP lysosomal trafficking is observed in FTLD patients with GRN mutations (Zhou et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This will be of therapeutic interest for FTLD, since haploinsufficiency of PGRN is a leading cause of FTLD and impaired PSAP lysosomal trafficking is observed in FTLD patients with GRN mutations (Zhou et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies have shown that PGRN and PSAP form a complex, both intracellularly and extracellularly, and facilitate each other's lysosomal delivery (Zhou et al . , ). Since both PGRN and PSAP are essential for proper lysosomal function and loss of function in either gene causes lysosomal storage diseases, more studies on the interaction of PGRN and PSAP will help us develop strategies to enhance the binding affinity between these two proteins and thus the activities of PGRN and PSAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PGRN is a growth factor‐like protein with neurotrophic properties in the brain (Van Damme et al , ). PGRN is also transported to lysosomes (Hu et al , ; Zhou et al , ) where it appears to regulate expression and activity of lysosomal proteins (Ahmed et al , ; Hu et al , ; Wils et al , ; Tanaka et al , ,b; Gotzl et al , , , ; Beel et al , ; Chang et al , ; Ward et al , ; Zhou et al , ). PGRN is proteolytically processed into granulin peptides, which can be found in biological fluids (Bateman et al , ; Shoyab et al , ; Belcourt et al , ; Cenik et al , ).…”
Section: Introductionmentioning
confidence: 99%